Rearing wolves to our own destruction : slavery in Richmond, Virginia, 1782-1865 - Takagi, Midori, 1962- (Charlottesville : University Press of Virginia, 1999)
Richmond was not only the capital of Virginia and of the Confederacy, it was also one of the most industrialized cities south of the Mason-Dixon Line. Boasting ironworks, tobacco-processing plants, and flour mills, the city by 1860 drew half of its male workforce from the local slave population. "Rearing Wolves to Our Own Destruction" examines this unusual urban labor system from 1782 until the end of the Civil War
Richmond's urban slave system offered blacks a level of economic and emotional support not usually available to plantation slaves. "Rearing Wolves to Our Own Destruction" offers a valuable portrait of urban slavery in an individual city that raises questions about the adaptability of slavery as an institution to an urban setting and, more importantly, the ways in which slaves were able to turn urban working conditions to their own advantage.
1 Inauspicious Beginnings 9 -- 2 The Road to Industrialization and the Rise of Urban Slavery, 1800-1840 16 -- 3 Behind the Urban "Big House" 37 -- 4 Maturation of the Urban Industrial Slave System, 1840-1860 71 -- 5 Formation of an Independent Slave Community 96 -- 6 The War Years, 1861-1865 124.
Includes bibliographical references (pages 168-179) and index.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Slavery -- Virginia -- Richmond -- History -- 18th century; Slavery -- Virginia -- Richmond -- History -- 19th century; Enslaved persons -- Virginia -- Richmond -- Social conditions; African Americans -- Virginia -- Richmond -- Social conditions; Richmond (Va.) -- History -- 18th century; Richmond (Va.) -- History -- 19th century; Esclaves -- Virginie -- Richmond -- Conditions sociales; Noirs américains -- Virginie -- Richmond -- Conditions sociales; SOCIAL SCIENCE -- Slavery; SOCIAL SCIENCE -- Ethnic Studies -- African American Studies; African Americans -- Social conditions; Slavery; Enslaved persons -- Social conditions; Virginia -- Richmond; Sklaverei; Richmond, Va; Slavernij; Geschichte 1782-1865.; 1700-1899; History